Analisis Kesalahan Berbahasa pada Teks Narasi Karya Siswa SMPN 4 Tasikmalaya - Purnama Sari, Elsa; Dzuhrisa, Mahanda; Febriyanti, Elysa; Nurjamilah, Ai Siti (Jurnal Bahasa, Sastra, dan Budaya, 2025)
The ability to speak correctly and according to the rules is one of the main skills that students need to have, especially at the junior high school (SMP) level. Language not only functions as a means of communication, but also as a thinking tool that influences the development of students' cognitive abilities. This research aims to examine various language errors made by junior high school students, including aspects of phonology, morphology, syntax and semantics. The approach used is descriptive qualitative with documentation methods and content analysis of student writing. The results of the research show that students often make mistakes in pronunciation, use of affixes, formation of sentence structures, and choosing the right words. It is hoped that these findings can help teachers and students recognize and correct these errors, so that language learning can take place more effectively.